2014
DOI: 10.1007/s10098-014-0869-6
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of azo dyes by laccase: biological method to reduce pollution load in dye wastewater

Abstract: Laccases are the oldest with low substrate specificity enzymes used for degradation of various compounds, especially, dyes. In the present investigation, the cell-free extract of laccase enzyme is applied to degrade azo dyes used in leather processing. The enzyme degrades the azo dyes rapidly at optimum growth conditions of pH 7.0, temperature 37°C and incubation duration of 72 h. Better production of the enzyme was achieved with dextrose, yeast extract, acetone, copper sulphate and orange peel. The molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(40 citation statements)
references
References 58 publications
0
40
0
Order By: Relevance
“…synthesize specific enzymes on the culture medium (Barrasa et al, 2014;Kanagaraj;Senthilvelan;Panda, 2015). For the P. ostreatus EF60 isolate, the increase in the methylene blue concentration reduced the mycelial diameter at 50 mg L -1 by 38.5%, and the mycelial growth was adjusted to a quadratic regression model.…”
Section: Mycelial Growth and Discoloration Of Methylene Blue In The Smentioning
confidence: 99%
See 3 more Smart Citations
“…synthesize specific enzymes on the culture medium (Barrasa et al, 2014;Kanagaraj;Senthilvelan;Panda, 2015). For the P. ostreatus EF60 isolate, the increase in the methylene blue concentration reduced the mycelial diameter at 50 mg L -1 by 38.5%, and the mycelial growth was adjusted to a quadratic regression model.…”
Section: Mycelial Growth and Discoloration Of Methylene Blue In The Smentioning
confidence: 99%
“…Kanagaraj, Senthilvelan and Panda (2015) reported that dyes, when degraded by bioremediation fungi, release ammonia, which is rapidly immobilized by microbial biomass and ensures mycelial growth, discoloration and dye degradation (Kundjadia et al, 2016).…”
Section: Discoloration Of Methylene Blue By Filamentous Fungi In the mentioning
confidence: 99%
See 2 more Smart Citations
“…Dye pollution reduction has been exhaustively studied for several years, yet, currently new technologies have been developed to perform and improve dye degradation, making the environment cleaner and reducing pollution. The main and new methods to reduce dye pollution involve activated carbon (GHAEDI et al, 2012), surface modified activated carbons (MOHAMMED et al, 2015), nanoadsorbents (KYZAS; MATIS, 2015), agricultural adsorbent waste (PELÁEZ-CID et al, 2013), other adsorbents (YAVUZ; SAKA, 2013), ozonation (CASTRO et al, 2016), irradiation (HERNÁNDEZ-URESTI et al, 2011), photocatalics (MAHMOODI, 2013, plasma discharge (JIANG et al, 2014), biological methods (KANAGARAJ et al, 2014) and others.…”
Section: Introductionmentioning
confidence: 99%